Hydrogeological Conditions of Qazaniyah Sub-basin in Diyala / Iraq - Muhsin, Zahraa. M.; Al-Kubaisi, Qusai .Y. (Iraqi Journal of Science, 2021)
The study area is located in the eastern part of the Diyala Governorate close to the Iraqi-Iranian border. This study was set to investigate the hydrogeological calculations of northeast of Qazaniyah wells where the groundwater moves in directions of from the northeastern parts towards the southwestern par, that is, the same direction of the topography and the same direction of the tendency of the layers t. The study‘s region is characterized by visible geological layers or those that can be penetrated to a reasonable depth by wells which are sedimentary rocks deposited in continental or semi-continental conditions in the bays. From the study of the hydraulic properties of the two hydrogeological and exemplary systems, the values of transmissivity, permeability and storage coefficient are ranged between 1.94- 5.73 m2/day, 1.02- 3.92 m/day and1.40 x 10-5- 2.62 x 10-4, respectively. While the estimated value of transmissivities, which are obtained from specific capacity, ranged between 6.27- 8.62 m2/day. This variance in the values indicates the broad differences in the values Lithology of aquifers, which seems to be influenced by the strength and the number of fractures and joints.